Redução de erros de exatidão em transformadores de corrente para medição de energia elétrica - Meneses, Leonardo Telino de (2017)
This research directs efforts and proposes a solution to mitigate errors of accuracy in spe-cific current transformers for electric energy measurement. Two solutions are developed: the first is a real-time control system that inhibits the supply of energy delivered to the CT – current transformer by its magnetic circuit and which withdraws this energy from the control circuit and no longer from the primary current being measured, inhibiting the pro-duction of the excitation current by the energy circulating in the primary of the current transformer; the second is the development of an error compensation algorithm based on the knowledge of the physical, electrical and magnetic characteristics of the current trans-former and the mass memory of the currents measured in the CT secondary, identifying the excitation current demanded in each integration interval, compensating this current and recalculating the measured energy. Laboratory tests demonstrate the validity of the first method with an error reduction level of more than 50%. Algorithm applications in mass memory of CTs demonstrate the validity of the second method. The theory and the practice are discussed and complement each other in the analytical, experimental and operational approaches carried out throughout the research.